A Generalized Theorem of the Maximum - Lawrence M. Ausubel; Raymond J. Deneckere (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1990)
This paper generalizes the Theorem of the Maximum (Berge, 1963) to allow for discontinuous changes in the domain and the objective function. It also provides a geometrical version of the (generalized) theorem.
Keywords: 330